Les solutions fondées sur la nature dans les territoires littoraux : une adaptation au changement climatique sans transformation ? - Julien Pelet; Guillaume Rieu (Développement Durable et Territoires)
Climate change and the threats it brings to coastal territories have recently led many scientists and international experts to propose relying on ecosystems to address this problem. Thus, after decades of deployment of technical solutions to protect and exploit the coastline, a new paradigm valuing "nature-based solutions"(NBS) seems to be emerging in coastal planning. On the basis of a survey conducted on climate and coastal risk policies in the Charente-Maritime department (France) during the decade following the Xynthia storm, we studied the development of NBS locally and its effects on public policies. After characterizing the local dynamics of the emergence of nature-based solutions in response to climate change adaptation and mitigation challenges, we analyze the changes induced by the implementation of these new approaches in coastal policies. Proposed only where the solution of dikes cannot be implemented or when they serve political interests, the development of NBS in Charente-Maritime leads to incremental changes in the public policies that they ultimately fail to transform.